Natural T cell–mediated protection against seasonal and pandemic Influenza: results of the Flu Watch cohort study - Hayward, Andrew C.; Wang, Lili; Goonetilleke, Nilu; Fragaszy, Ellen B.; Bermingham, Alison; Copas, Andrew; Dukes, Oliver; Millett, Elizabeth R.C.; Nazareth, Irwin; Nguyen-Van-Tam, Jonathan S.; Watson, John M.; Zambon, Maria; et al. (American Thoracic Society, 2015)
Rationale: A high proportion of influenza infections are asymptomatic. Animal and human challenge studies and observational studies suggest T cells protect against disease among those infected, but the impact of T-cell immunity at the population level is unknown.